Inotropic actions of protein kinase C activation by phorbol dibutyrate in guinea-pig isolated ventricular myocytes. - Mamas, M; Terrar, D (2001)
The mechanisms which underlie the inotropic actions of phorbol dibutyrate (PDBu), a synthetic compound which can directly activate protein kinase C (PKC), were investigated in guinea-pig isolated ventricular myocytes. Exposure of cells to PDBu (10(-7) M) reduced myocyte contraction amplitude to 46 +/- 3% of control (n = 8; P < 0.05) with an associated shortening in action potential duration (action potential duration at 90% repolarisation (APD90) was reduced to 83 +/- 1% of control; P < 0.05). The negative inotropic actions of PDBu and the shortening in action potential duration were abolished in the presence of a selective PKC inhibitor, Ro31-8220. Calcium transients (constructed from calcium-activated tail currents following interruption of action potentials by voltage clamp to -70 mV) were reduced following exposure to 10(-7) M PDBu by 38 +/- 2% (n = 9, P < 0.05). L-type calcium currents were not significantly altered following exposure to 10(-7) M PDBu (98 +/- 2% of control; P > 0.05). In contrast, delayed rectifier potassium currents (I(K)) were enhanced to 154 +/- 8% of control (n = 7; P < 0.05) by 10(-7) M PDBu. This enhancement of I(K) may contribute to the observed shortening in action potential duration observed following exposure to PDBu under the conditions of our experiments. When the action potential configuration was maintained throughout the experiment by applying a voltage-clamp waveform, 10(-7) M PDBu still reduced contraction amplitude to 57 +/- 3% of control (P < 0.05). Exposure to 10(-7) M PDBu also suppressed spontaneous activity (both spontaneous potential fluctuations induced by the beta-adrenergic agonist isoprenaline (40 nM), and transient inward currents induced by the cardiac glycoside ouabain (1 microM) under voltage clamp). It therefore appears that the reduction in myocyte contraction amplitude induced by exposure to PDBu may result in part through mechanisms independent of action potential shortening, which may include direct actions of protein kinase C on the function of the sarcoplasmic reticulum (SR) calcium store and/or on contractile proteins (though action potential shortening would be expected to cause a further decrease as a consequence of reduced calcium loading of the SR). The reduction of spontaneous activity caused by PDBu may also result from changes in the function of the SR store mediated by protein kinase C.